Ownership Structure and Corporate Governance as The Affecting Factors of Liquidity Policy in Consumption Goods Industry Sector Companies in Indonesian Stock Exchange - Erric Wijaya; Dita Noviany (Jurnal Ilmu Manajemen & Ekonomika, 2017)
This study discusses the influence of ownership structure and corporate governance as affecting factors to liquidity policy in consumer goods industry sector of companies listed in Indonesia Stock Exchange. The dependent variable in this research is liquidity policy which can be proxied with cash holdings, while the independent variables in this research are: ownership structure that can be proxy by insider ownership and foreign ownership, and corporate governance which can be proxy by with variable board size and board composition, firm size and growth sales as a variable control. This research uses multiple linear regression method with panel data approach. The sample used 21 companies in manufacturing industry which classified into consumer goods sector during the period 2012-2015. The result of the research shows that the variable of ownership structure is only variable insider ownership which has influence to cash holding. While from the corporate governance variable, it is only board size that affect cash holding. The value of adjusted R squared in this study amounted to 92.6%.